Investigation and Evaluation of COVID-19 Response by Purdue University of Fort Wayne in Welcoming Back Students - Boylan, Daniel H.; Kostic, Semir (Journal of Applied Business and Economics, 2023)
This research investigates the success of Purdue University, Fort Wayne’s Campus Kickoff event in the middle of the COVID-19 Pandemic and the planning to minimize the spread and infection. Researchers observed the attending student population, along with the presence of the virus on campus to determine the precautions effectiveness. Purdue University, Fort Wayne committed a normal approach while other campuses moved online. After examining the school’s infections before and after the Campus Kickoff event, we have discovered infection rates across campus proved there was no significant outbreak because of the event, meaning the prevention measures show to have been successful.